Ider Bumi: Daya Tarik Pariwisata Budaya - YAZID, hikmal (Jurnal Penelitian Ilmu Pariwisata, 2025)
Banyuwangi, as the eastern gateway of Java Island, is rich in natural beauty and cultural heritage. One of the prominent celebrations is Ider Bumi, which serves as a symbol of the fusion of local traditions and Islamic values. This study aims to explore the potential of Ider Bumi as a cultural tourism attraction in Banyuwangi. The method used is qualitative analysis with a case study approach. The qualitative analysis approach with a case study was chosen in this study because the Ider Bumi celebration in Banyuwangi is a unique cultural phenomenon and has a deep local context, which requires a comprehensive and detailed understanding. The results of the study show that Ider Bumi not only maintains cultural traditions, but also attracts tourists with art performances, culinary specialties, and cultural parades. This celebration has succeeded in creating an authentic cultural experience for visitors, thus potentially increasing tourist visits to Banyuwangi. In conclusion, Ider Bumi can be used as a strategy for developing sustainable cultural tourism, by involving local communities and promoting the uniqueness of Banyuwangi culture. This research is expected to contribute to efforts to preserve culture while improving the regional economy through tourism.